Nuclear medicine in the assessment and prevention of cancer therapy-related cardiotoxicity: prospects and proposal of use by the European Association of Nuclear Medicine (EANM) - Totzeck Matthias; Aide Nicolas; Bauersachs Johann; Bucerius Jan; Georgoulias Panagiotis; Herrmann Ken; Hyafil Fabien; Kunikowska Jolanta; Lubberink Mark; Nappi Carmela; Rassaf Tienush; Saraste Antti; et al. (Springer, 2022)
Cardiotoxicity may present as (pulmonary) hypertension, acute and chronic coronary syndromes, venous thromboembolism, cardiomyopathies/heart failure, arrhythmia, valvular heart disease, peripheral arterial disease, and myocarditis. Many of these disease entities can be diagnosed by established cardiovascular diagnostic pathways. Nuclear medicine, however, has proven promising in the diagnosis of cardiomyopathies/heart failure, and peri- and myocarditis as well as arterial inflammation. This article first outlines the spectrum of cardiotoxic cancer therapies and the potential side effects. This will be complemented by the definition of cardiotoxicity using non-nuclear cardiovascular imaging (echocardiography, CMR) and biomarkers. Available nuclear imaging techniques are then presented and specific suggestions are made for their application and potential role in the diagnosis of cardiotoxicity.